2017
DOI: 10.1186/s13048-017-0365-9
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of clinical response to drugs in ovarian cancer using the chemotherapy resistance test (CTR-test)

Abstract: BackgroundIn order to validate if the test result of the Chemotherapy Resistance Test (CTR-Test) is able to predict the resistances or sensitivities of tumors in ovarian cancer patients to drugs, the CTR-Test result and the corresponding clinical response of individual patients were correlated retrospectively. Results were compared to previous recorded correlations.MethodsThe CTR-Test was performed on tumor samples from 52 ovarian cancer patients for specific chemotherapeutic drugs. Patients were treated with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Another approach for predicting the response to chemotherapy is to perform in vitro growth assays using fresh tumor samples exposed to chemotherapy [11]. The sensitivity and specificity of these in vitro assays vary, but they do show promise as a possible means to predict patient response, although they have not yet had widespread use in a clinical setting [12,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Another approach for predicting the response to chemotherapy is to perform in vitro growth assays using fresh tumor samples exposed to chemotherapy [11]. The sensitivity and specificity of these in vitro assays vary, but they do show promise as a possible means to predict patient response, although they have not yet had widespread use in a clinical setting [12,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…However, the majority of patients eventually become resistant to chemotherapeutic drugs and this causes the prognosis of these patients to be unsatisfactory ( 20 ). Previous studies for ovarian cancer were primarily based on cells generated from primary lesions ( 21 , 22 ), and few of these studies focused on the omentum ( 23 ). It has been suggested that metastatic cancer is a markedly heterogeneous disease at the genetic, transcriptomic and microenvironment levels ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Once chemoresistance occurs, few therapeutic options exist. Moreover, studies reported that chemotherapy resistance is associated with poor prognosis [ 6 ] and tumor relapse [ 7 , 8 ]. Understanding the mechanisms of chemoresistance is crucial for finding new strategies and better cancer therapy.…”
Section: Introductionmentioning
confidence: 99%